Bakat di pacu nilai Kementerian Pendidikan Malaysia [video recording] - 495834 Universiti Teknologi Malaysia; Wahid Omar, Prof. Dato', 1962- (Skudai : Universiti Teknologi Malaysia, 2015)
Interview with Prof. Datuk Ir. Dr. Wahid bin Omar, Naib Canselor UTM about education aspiration and national education development program,